Direct adhesion to bone marrow stroma via fibronectin receptors inhibits hematopoietic progenitor proliferation. - Hurley, R W (1995)
In long-term bone marrow cultures, stroma-adherent progenitors proliferate significantly less than nonadherent progenitors. Thus, close progenitor-stroma interactions may serve to regulate or restrict rather than promote hematopoietic progenitor proliferation. We hypothesized that signaling through adhesion receptors on hematopoietic cells may contribute to the inhibition of proliferation observed when progenitors are in contact with stroma. We demonstrate that progenitors cultured physically separated from stroma in a transwell proliferate significantly more than progenitors adherent to stroma. Furthermore, proliferation of colony forming cells (CFC) is reduced after specific adhesion to stroma, metabolically inactivated glutaraldehyde-fixed stroma, stromal-extracellular matrix, or the COOH-terminal heparin-binding domain of fibronectin. Nonspecific adhesion to poly-L-lysine fails to inhibit CFC proliferation. That the VLA-4 integrin is one of the receptors that transfers proliferation inhibitory signals was shown using blocking anti-alpha 4 monomeric F(ab) fragments. Furthermore, when synthetic peptides representing specific cell attachment sites within the heparin-binding domain of fibronectin were added to Dexter-type marrow cultures, significantly increased recovery and proliferation of CFC was observed, suggesting that these peptides disrupt adhesion-mediated proliferation inhibitory events. Thus, negative regulation of hematopoiesis may not only depend on the action of growth inhibitory cytokines but also on growth inhibitory signals resulting from direct adhesive interactions between progenitors and marrow stroma.